Students’ perceptions and challenges in using YouTube to improve speaking in learning English - Nafi Ghifary, Yazid; Seinsiani, Izzati Gemi (ELT Forum: Journal of English Language Teaching, 2025)
Continued improvements in globalization and modern-day developments have also led to an increase in technology use within education. The Internet offers an array of information and resources which can be accessed effortlessly. With the emergence of video sharing platforms like YouTube, there is now an unprecedented and innovative method of learning. Both teachers and students are now able to enhance their English speaking skills through interesting and authentic multimedia which greatly improves comprehension. The aim of this study is to explore the issues that come with YouTube integration in education and examine the students’ and teachers’ attitudes concerning its use for learning activities geared towards fluency and pronunciation, as well as the enhancement of their skills. This research employs qualitative descriptive methods. Open-ended questionnaires were given to students in an Indonesian university to collect in-depth information about language learning and the use of YouTube in classes. In addition, the interviews were conducted to gain in-depth insights and experiences concerning the subject matter. The study concluded that although there were some YouTube technical issues, students maintained a positive attitude towards the use of YouTube, and speaking advanced fluency and pronunciation skills greatly improved. Furthermore, this research recommends that YouTube be used as an instructional medium supervised by the teacher, to enhance the learning process to be more interesting, enjoyable, and productive.